A Comparative Survey on Islamic Riba and Western Usury (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO 1. Introduction - 2. Premise - 3. Ancient history - 4. Roman law - 5. Aquinas and Canon law - 6. 16th Century: Protestantism and the mercantile era - 7. 17th century: Jusnaturalism - 8. 18th century and 19th centuries: industrialization and capitalism - 9. The prohibition of riba - 10. Similarities between the sharia prescriptions and the ancient Jewish ones - 11. Riba and its recent openings - 12. Riba prohibition in the twentieth century and the sharia-compliant financial instruments - 13. Solutions - 14. Islamic Finance - 15. Conclusions.ABSTRACT: The article addresses the theme of usury taking into account various viewpoints and traditions, pausing in particular on the Western and Islamic notions of lending at interest, in order to outline its distinctive features in the present days as well as throughout its historical evolution. The author applies a comparative research method, examining both the differences and similarities between the Western and Muslim concept of usury so to present an accurate picture of the phenomenon. In fact, the article aims at answering the latest questions concerning the possibility for the Muslim model to be a valuable resource in overcoming the keep going financial crisis.
Keywords: Islam